IMPROVING FISH SUPPLY CHAIN VALUE THROUGH REVERSE LOGISTICS MANAGEMENT AT EAST JAVA PROVINCE - Naufal Aqiel Fitrachman; Mustaruddin; Gondo Puspito; Zulkarnain; Ateng Supriatna; Thomas Nugroho; Muhammad Zaky Arkan (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
This study identifies major problems in the fisheries supply chain in East Java Province, where the capture fishing sector faces challenges such as a high number of rejected fish and a lack of effective waste management. Therefore, this research aims to identify the structure of the fish supply chain and value enhancement through reverse logistics, as well as to formulate strategies to optimize the supply value chain to increase efficiency and added value for all parties involved. The study used a descriptive method with qualitative and quantitative approaches, analyzed using reverse logistics and the USG (Urgency, Seriousness, Growth) method. The analysis shows that implementing reverse logistics effectively creates added value, with processed fishery waste products like crackers reaching a value of Rp18,500 per kilogram and waste management efficiency reaching Rp4,355,000 per day. Based on the USG analysis, the most optimal strategies are capacity building for supply chain actors (PPRT) and the development of integrated waste processing facilities (SPLT), which are key to optimizing the economic value of the entire chain, from fishing port to consumer. Key words: fishery, fish logistic, fishing port, industry, waste